IMPLEMENTASI FUZZY TOPSIS DALAM PERENCANAAN STRATEGI BISNIS - Wulandari, Fera Tri (SENATIK STT Adisutjipto, 2013)
Strategic planning is done in order to the company can look at it objectively internal and external conditions that the company can anticipate changes in the external environment. Strategic planning begins with the introduction of the company's vision and mission in order to determine which company will produce an overview of the internal and external environment. Furthermore conduct a SWOT analysis to formulate appropriate strategic alternatives to position the company. The last stage is the decision-making strategies using Fuzzy Quantitive Strategic Planning Matrix (FQSPM) to determine and select the best strategy from a number of alternative strategies given certain criteria using Fuzzy Technique for Order Preference by Similarity to Ideal. Solution (FTOPSIS). Results of the determination of the strategy chosen by the fuzzy TOPSIS for furniture company is intelegent increased marketing and promotional products.